Standardizing DIRAC's cloud interfaces - Bauer,D; Fayer,S (EDP Sciences, 2024)
DIRAC is a widely used framework for distributed computing. It provides a layer between users and computing resources by offering a common interface to a number of heterogeneous resource providers. In these proceedings we describe a new implementation of the DIRAC to Cloud interface.